2020
DOI: 10.1186/s12978-020-0883-6
|View full text |Cite
|
Sign up to set email alerts
|

Concerns and educational needs of Iranian parents regarding the sexual health of their male adolescents: a qualitative study

Abstract: Background: Parents play an important role in promoting the sexual health of their adolescents. However, many parents experience several challenges. The purpose of this study was to explore the concerns and educational needs of Iranian parents regarding the sexual health of their male adolescents. Methods: This qualitative study was designed based on the conventional content analysis approach. Semistructured and in-depth interviews were conducted with 16 parents of male adolescents aged 12-18 years. All interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
3
16
0
1
Order By: Relevance
“…Revising the laws according to the needs of the society, and informing the judges about the differences in the issuance of sentences for different sexual orientations (homosexual, gender dysphonia), sexual offenders and sexual patients (paraphilia) were also suggested as the reasons for cooperating with the judicial organization (40,52). Our ndings, in accordance with previous studies (24,42,53), indicated a dual role for the media and cyberspace. The participants suggested that the media, especially the state television, should take measures to break the taboo around sexuality.…”
Section: Information and Motivationsupporting
confidence: 90%
See 2 more Smart Citations
“…Revising the laws according to the needs of the society, and informing the judges about the differences in the issuance of sentences for different sexual orientations (homosexual, gender dysphonia), sexual offenders and sexual patients (paraphilia) were also suggested as the reasons for cooperating with the judicial organization (40,52). Our ndings, in accordance with previous studies (24,42,53), indicated a dual role for the media and cyberspace. The participants suggested that the media, especially the state television, should take measures to break the taboo around sexuality.…”
Section: Information and Motivationsupporting
confidence: 90%
“…Empowerment of parents regarding sexuality education is an effective intervention for promoting the adolescents' sexual health (21,24,39,40). Therefore, sensitizing parents, encouraging their interaction with the school, and empowering them in order to reduce their resistance against formal education were among the suggestions proposed by teachers and policymakers.…”
Section: Information and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported previously (37-39), a combination of individual, family, religious, and socio-political factors can in uence the people's perceptions of sexuality education and its acceptance at the national level. Similar to previous studies, this study showed empowerment of parents regarding sexuality education is an effective intervention for promoting the adolescents' sexual health (22,26,40,41). Therefore, sensitizing parents, encouraging their interaction with the school, and empowering them in order to reduce their resistance against formal education were among the suggestions proposed by teachers and policymakers.…”
Section: Informationsupporting
confidence: 84%
“…They have made several achievements in combating HIV/AIDS, with the focus on injectable drug users, but have countered a series of challenges and gaps in the determination of violence against women prevalence, gender equality, the increase of high risk behaviour in adolescents and sexual education for them (25). Babayanzad et al (2020) also underlined the need for sexual health education for students, teachers, instructors, and school authorities to meet the needs of the parents of adolescent boys in Iran (26). Because of acquiring information and sexual health skills can help change adolescents' attitudes and responsible behaviors (27)(28)(29),so interventions based on information, motivation and behavioral skills model (IMB) are recommended for sexual health (29,30).…”
Section: Introductionmentioning
confidence: 99%